First record of the intermediate scabbardfish Aphanopus intermedius (Scombriformes: Trichiuridae) in the western South Atlantic Ocean. Issue 5 (31st October 2018) - Eduardo, Leandro N.; Villarins, Bárbara T.; Lucena‐Frédou, Flávia; Frédou, Thierry; Lira, Alex S.; Bertrand, Arnaud; Mincarone, Michael M.
Abstract : This study reports on the first record of the intermediate scabbardfish Aphanopus intermedius in the western South Atlantic Ocean, based on a single specimen 725 mm standard length collected between 0 and 610 m depth around Rocas Atoll off north‐eastern Brazil. Measurements and counts are provided and compared with those available in the literature.